Актуальні заходи антиінфляційної політики на сучасному етапі - Яковенко, Р. В.; Yakovenko, R.; Чередніченко, М. Г.; Cherednichenko, M. (Praha : Publishing House „Education and Science” s.r.o., 2012)
У тезах визначено традиційні та специфічні заходи подолання інфляції в Україні на сучасному етапі The theses identify the traditional and specific measures to overcome inflation in Ukraine at the present stage
Topical measures of anti-inflationary policy at the present stage
Keywords: облікова ставка; інфляційні процеси; здешевлення кредитних ресурсів; операції на відритому ринку; accounting rate; inflation processes; cheaper credit resources; operations in the open market